Generations at work : managing the clash of veterans, boomers, xers, and nexters in your workplace / Ron Zemke; Claire Raines; Bob Filipczak - Zemke, Ron
Written by a team of distinguished cross-generational authors, this groundbreaking book supplies fresh, provocative insights & practical solutions for understanding differences, resolving conflicts & managing effectively in today's age-diverse workplace. For anyone struggling to manage people who just don't see work (or life) the same way, this book helps you understand the gulf that separates the generations